4D Biomaterials for Light‐Guided Angiogenesis. (17th December 2018) - Farrukh, Aleeza; Paez, Julieta I.; del Campo, Aránzazu
Abstract: A strategy for spatial and temporal regulation of ligand presentation within a biomaterial, and the consequent site‐ and time‐specific cellular responses in 4D cell cultures are presented. The key molecular component is a light‐activatable adhesive peptidomimetic (cyclo Arg‐Gly‐Asp‐phe‐Cys, RGDfC) modified with the two‐photon photocleavable group ( p ‐methoxynitrobiphenyl, PMNB) used to functionalize a hydrogel. A scanning laser at 740 nm defines the 4D presentation of active RGD ligands within the gel, and directs basic cellular processes of embedded cells in situ. The excellent photochemical properties of the PMNB photoremovable group allows direct photomanipulation of the cellular environment without appreciable damage of the embedded cells. Light‐directed migration of fibroblasts within a crosslinked poly(ethylene glycol) (PEG) hydrogel, and sequential, light‐regulated angiogenesis with human umbilical vein endothelial cells (HUVECs) in 4D constructs is demonstrated. The materials presented here represent unique microenvironments to reconstruct dynamic changes in the composition of the extracellular space of cells that occur in in vivo tissues. Abstract : A biomaterial functionalized with a two‐photon activatable RGD motif allows in situ, light‐triggered cell–material interactions in a 4D context. Cellular attachment, migration, and angiogenic differentiation of endothelial cells within a hydrogel are regulated with spatiotemporal control.